“The effects of demarketing campaigns on consumption and consumer behaviour. A study of smokers in the UK - Nanji, Naveed Firoz (2015)
Tobacco consumption is a controversial habit in society and has been heavily demarketed throughout the years due to the effects it causes consumers. Governments together with social marketers have attempted to reinforce these campaigns through increase in prices, changing packaging regulations and reducing availability of these products to the public on the governments’ side and social marketers have set out anti-smoking campaigns to educate consumers on the dangers of smoking. Advertising on marketing has two kinds of emotional appeals that they use to reinforce this, negative and positive appeals in advertising. Using fear as the main negative attempts to put consumers in discomfort and the only way to remove one from that discomfort is to stop the behaviour. Positive appeals tend to target the understanding side of emotion for consumers. The aim of this study is to find out the effects of demarketing campaigns on consumption and consumer behaviour. The study of smokers in the UK. The study will also consider consumer involvement with the product and attempt to understand if there is a relationship between consumer involvements in advertising. Due to the lack of research done on this particular topic, this will be an exploratory study and add value to previous research done. This will be uncovered by conducting qualitative interviews with smokers of different levels of involvement with the product and consumption. This data will be will be interpreted, transcribed and analysed very comprehensively to meet objectives of the study. Scope of the study will be based upon London and Nottingham.